Damned Women : Sinners and Witches in Puritan New England - Reis, Elizabeth, 1958- (Book collections on Project MUSE., 1997)
Following the Salem witchcraft trials, Reis argues, Puritans' understanding of sin and the devil changed. Women and men took more responsibility for their sins and became increasingly confident of their redemption, yet women more than men continued to imagine themselves as essentially corrupt, even after the Great Awakening.